Typo-chronological evolution of iron arrowheads of the X–XV centuries from the territory of Northern Belarus - Plavinski, Uladzimir A. (Journal of the Belarusian State University. History, 2017)
From the territory of Northern Belarus, there are at least half a barrel of iron arrowheads and a crossbow of the X–XV centuries. Considering the entire array of findings, we can distinguish several stages of the evolution of the terminal complex. For the X–XI centuries the most characteristic types of arrows are the double-sculled, petiolate, petiolate with a lanceolate-shaped, rhombic, laurel-like shape. In the XII–XIII centuries it is necessary to expand the typological assortment of arrowheads, including the widely used types intended for firing from composite onions, which allows to judge its active use this time. The number of armor-piercing tips intended for piercing annular and plate armor increases. From the middle of the XIII century on the territory of Belarus are spread petiolate arrowheads of Mongolian types, which was the result of the spread of Mongolian technological traditions in the territory of Rus. From the second half of XIII – the first half of the XIV century unification and reduction of the typological assortment of arrows is observed, the number of brane-piercing tips is increasing, but flat ones remain dominant. There is a slight spread of crossbow weapons, which was the result of occasional contacts with the Crusaders.